Genomic Heterogeneity and O-Antigenic Diversity of Campylobacter upsaliensis and Campylobacter helveticus Strains Isolated from Dogs and Cats in Germany - Moser, I. (American Society for Microbiology, 2001)
A serotyping scheme based on heat-stable surface antigens was established for 101 Campylobacter upsaliensis and 10 Campylobacter helveticus strains isolated from 261 dogs and 46 cats of different ages originating from two geographically distinct regions in Germany. The prevalence of C. upsaliensis varied between 27.8% in juvenile dogs (<12 months of age) and 55.4% in adult dogs (P < 0.05). Of the cats, 19.6% harbored C. upsaliensis, whereas 21.7% carried C. helveticus. Of the C. upsaliensis isolates from both host species, 93.1% belonged to five different serogroups, two of them being prevalent at rates of 47.5 and 27.7%, with different frequencies in both regions. Six (54.6%) of the C. helveticus isolates also belonged to serotypes found among C. upsaliensis strains, whereas five (45.4%) possessed an O antigen unique for C. helveticus. In contrast, a considerable degree of genomic diversity of the isolates was assessed by macrorestriction analyses with the endonucleases SmaI and XhoI, using pulsed-field gel electrophoresis as well as enterobacterial repetitive intergenic consensus sequence PCR (ERIC PCR). Restriction with SmaI pointed towards the existence of clonal groups associated to some extent with serotypes, while restriction with XhoI disintegrated these groups to smaller noncoherent subgroups. Analysis of ERIC PCR profiles did not exhibit any associations with serotypes. In conclusion these data demonstrate the genomic heterogeneity among C. upsaliensis strains and indicate that the combination of SmaI restriction with serotyping is a useful tool to investigate the expansion of clonal groups of C. upsaliensis.